On the Westward Shift and Strengthening of the Atmosphere‐To‐Ocean Bjerknes Feedback in the Tropical Pacific Since 2000 - Zongrong Li; Ruiqiang Ding; Jiangyu Mao; Zhengyi Ren; Jianping Li (Geophysical Research Letters)
Abstract The behavior of the El Niño–Southern Oscillation (ENSO) has undergone significant changes since the year 2000. Meanwhile, a notable westward shift and strengthening in the atmosphere‐to‐ocean Bjerknes feedback were observed. We find that this shift can be primarily attributed to a weakened relationship between the zonal gradient of precipitation anomaly and that of sea surface temperature (SST) anomaly since 2000.This weakened relationship is a comprehensive manifestation of reduced El Niño‐related precipitation anomalies in the central‐eastern tropical Pacific and increased anomalies in the western tropical Pacific. These changes are connected to the mean state change in the tropical Pacific after 2000, where the cooler background SSTs in the central‐eastern tropical Pacific suppress upward motion, and the warmer background SSTs in the western tropical Pacific promote upward motion in the overlying atmosphere. Our findings offer a potential explanation for the westward shift and strengthening in the atmosphere‐to‐ocean Bjerknes feedback since 2000.